Early stage blunting causes rapid reductions in stone tool performance. (March 2018) - Key, Alastair; Fisch, Michael R.; Eren, Metin I.
Abstract: Palaeolithic stone technologies have never been investigated in terms of how sharpness influences their ability to cut. In turn, there is little understanding of how quickly stone cutting edges blunt, how past populations responded to any consequent changes in performance, or how these factors influenced the Palaeolithic archaeological record. Presented here is experimental data quantitatively detailing how variation in edge sharpness influences stone tool cutting performance. Significant increases in force (N) and material displacement (mm) requirements occur rapidly within early stages of blunting, with a single abrasive cutting stroke causing, on average, a 38% increase in the force needed to initiate a cut. In energetic terms, this equates to a 70% increase in work (J). Subsequent to early stages of blunting we identify a substantial drop in the impact of additional edge abrasion. We also demonstrate how edge (included) angle significantly influences cutting force and energy requirements and how it co-varies with sharpness. Amongst other conclusions, we suggest that rapid reductions in performance due to blunting may account for the abundance of lithic artefacts at some archaeological sites, the speed that resharpening behaviours altered tool forms, and the lack of microscopic wear traces on many lithic implements. Highlights: Influence of edge sharpness on stone tool cutting performance is quantified. Work (J) and force (N) requirements rapidly increase during early stage blunting. A single blunting event increased required cutting force by 38% and work by 70%. Influence of sharpness on cutting efficiency demonstrated to covary with edge angle. Blunting helps explain artefact accumulation, resharpening, and microwear levels.